2010
DOI: 10.1083/jcb.201005140
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin microdomains interact with the cortical cytoskeleton to control uropod formation and neutrophil recruitment

Abstract: The association between flotillin microdomains and the cortical cytoskeleton controls myosin IIa activation and neutrophil chemotaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
119
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(135 citation statements)
references
References 48 publications
(53 reference statements)
15
119
1
Order By: Relevance
“…The above results indicated that flotillin microdomains underwent a re-ordering triggered by capacitation in the guinea p i g sper m. Sub seque ntly, w e pe rformed coimmunoprecipitation assays to determine whether spectrin and flotillin-1 were associated in the guinea pig sperm, as proposed in other cell types (Head et al 2014;Ludwig et al 2010;Salzer and Prohaska 2001). The Western blot analysis of co-immunoprecipitated proteins revealed that spectrin coimmunoprecipitated together with flotillin-1 in noncapacitated sperm, whereas in capacitated sperm, a significantly lower amount of spectrin co-immunoprecipitated with flotillin-1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The above results indicated that flotillin microdomains underwent a re-ordering triggered by capacitation in the guinea p i g sper m. Sub seque ntly, w e pe rformed coimmunoprecipitation assays to determine whether spectrin and flotillin-1 were associated in the guinea pig sperm, as proposed in other cell types (Head et al 2014;Ludwig et al 2010;Salzer and Prohaska 2001). The Western blot analysis of co-immunoprecipitated proteins revealed that spectrin coimmunoprecipitated together with flotillin-1 in noncapacitated sperm, whereas in capacitated sperm, a significantly lower amount of spectrin co-immunoprecipitated with flotillin-1 (Fig.…”
Section: Resultsmentioning
confidence: 85%
“…We have shown that, by inhibiting spectrin cytoskeleton cleavage via calpain, the normal course of the acrosome reaction is blocked in guinea pig sperm (Bastian et al 2010). Interestingly, flotillin microdomains have the property of spatially organizing the plasma membrane and allowing specifically located signaling (i.e., active SFKs) by interacting with the cell cortical cytoskeleton, specifically with actin, spectrin and myosin 2a (Langhorst et al 2007;Ludwig et al 2010). Significant aggregation of flotillin-1 in the apical acrosomal region has been reported as being a capacitation marker in boar sperm (van Gestel et al 2005); however, the mechanisms regulating such an aggregation and its involvement in capacitation and the acrosome reaction have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this view was challenged since other investigators could not find a reggie-dependent endocytosis of GPI-anchored proteins nor was the emergence of caveola-like indentationsreported to be formed in Hela cells after reggie-1 and -2 overexpression for endocytosis (Frick et al 2007)-observed by other laboratories (Kirkham et al 2008;Langhorst et al 2008a;Lundmark et al 2008;Schneider et al 2008; and our own unpublished data). Also, the recently published reggie-2 knock-out mouse did not show the expected defect (Ludwig et al 2010). From our point of view, several observations speak for a reggie-mediated cargo transport (which includes the recycling compartment) towards the plasma membrane.…”
Section: Reggie/flotillin At Trafficking Vesicles and In Lysosomesmentioning
confidence: 84%
“…Our own unpublished work has demonstrated that expression of dominant-negative forms of specific Rho-GTPases, which co-exist with reggies on specific tubules and vesicles and regulate vesicle sorting and trafficking, causes loss of reggie from these tubules/vesicles and promotes delivery of reggie to lysosomes. It has, moreover, been observed that downregulation of reggie-1 in Hela and N2a cells by siRNAs leads to the degradation of reggie-2 (Solis et al 2007) while others have reported vice versa (Ludwig et al 2010). Together with the fact that reggies form homo-and hetero-oligomers, their joined up-and downregulation suggests that they are perhaps scaffolds of a dynamic tubulo-vesicular compartment whose abundance and efficacy seems to depend on the available concentration of reggie-1 and reggie-2.…”
Section: Reggie/flotillin At Trafficking Vesicles and In Lysosomesmentioning
confidence: 96%